Unless Reasoning - Carriedo, Nuria; Moreno-ríos, Sergio; Schaeken, Walter; García-madruga, Juan A.; Gutiérrez, Francisco (The Spanish Journal of Psychology, 2008)
We report the results of two experiments investigating conditional inferences from conditional unless assertions, such as Juan is not in León unless Nuria is in Madrid. Experiments 1 and 2 check Fillenbaum’s hypothesis about the semantic similarity of unless with if not and only if assertions; both also examine inferential endorsements (Experiment 1) and endorsements and latencies (Experiment 2) of the four logically equivalent conditional formulations: if A then B, if not-B then not-A, A only if B and not- A unless B. The results of these experiments show the similarity of unless and only if, confirming that the representation of both conditionals from the outset probably include two possibilities directionally oriented from B to A; results also confirm the especial difficulty of unless assertions. The implications of the results are discussed in the context of recent psychological and linguistic theories of the meaning of unless.